Associations between emphysema-like lung on CT and incident airflow limitation: a general population-based cohort study. Issue 5 (26th October 2017) - Oelsner, Elizabeth C; Smith, Benjamin M; Hoffman, Eric A; Folsom, Aaron R; Kawut, Steven M; Kaufman, Joel D; Manichaikul, Ani; Lederer, David J; Schwartz, Joseph E; Watson, Karol E; Enright, Paul L; Austin, John H M; et al.
Abstract : Emphysema on CT is associated with accelerated lung function decline in heavy smokers and patients with COPD; however, in the general population, it is not known whether greater emphysema-like lung on CT is associated with incident COPD. We used data from 2045 adult participants without initial prebronchodilator airflow limitation, classified by FEV1 /FVC<0.70, in the Multi-Ethnic Study of Atherosclerosis. Emphysema-like lung on baseline cardiac CT, defined as per cent low attenuation areas<—950HU >upper limit of normal, was associated with increased odds of incident airflow limitation at 5-year follow-up on both prebronchodilator (adjusted OR 2.62, 95% CI 1.47 to 4.67) and postbronchodilator (adjusted OR 4.38, 95% CI 1.63 to 11.74) spirometry, independent of smoking history. These results support investigation into whether emphysema-like lung could be informative for COPD risk stratification.